Skin Avulsion Injuries with Use of Adhesive Surgical Drapes - Liu, Yitao; Nandi, Sumon; Skaife, Tyler; Lang, Jason; Bono, James V. (The Journal of Knee Surgery, 2013)
Iodophor-impregnated adhesive drapes are commonly used to reduce the incidence of surgical site infections (SSI).While proper and discretionary use of drapes can provide significant benefit, there are potential risks. We present two cases of degloving injuries sustained from use of these drapes during total knee arthroplasty. The patients, deemed high risk for potential skin avulsion injuries, received standard wound care and close follow-up which resulted in healing of the lesions at 6-week follow-up.
Keywords: adhesive drapes; total knee arthroplasty; degloving injuries